2017
DOI: 10.9790/1959-0603085060
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors Affecting Postoperative Quality of Recovery for Patients Undergoing Surgery

Abstract: The assessment of quality of recovery after surgery and anesthesia is considered an important issue because it provides information that could help to identify problems that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
2
Order By: Relevance
“…Rahman ve ark. 15 erkeklerin postoperatif iyileşme kalitesinin kadınlara göre daha iyi düzeyde olduğunu belirlemişlerdir. Yolcu ve Akın'ın çalışmasında 16 kadın hastaların mobilizasyon konusunda erkek hastalara göre desteklenme ihtiyacının daha fazla olduğu belirlenmiştir.…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation
“…Rahman ve ark. 15 erkeklerin postoperatif iyileşme kalitesinin kadınlara göre daha iyi düzeyde olduğunu belirlemişlerdir. Yolcu ve Akın'ın çalışmasında 16 kadın hastaların mobilizasyon konusunda erkek hastalara göre desteklenme ihtiyacının daha fazla olduğu belirlenmiştir.…”
Section: Tartişma Ve Sonuçunclassified
“…Rahman ve ark. 15 ortopedi hastalarında postoperatif iyileşme kalitesinin genel cerrahi hastalarına göre daha zor olduğunu belirlemişlerdir. Başka bir çalışmada fiziksel olarak daha az aktif olan hastalarda ameliyat sonrası komplikasyon görülme oranının ve hastaneye yeniden yatışların daha fazla olduğu bulunmuştur.…”
Section: Tartişma Ve Sonuçunclassified
“…Importantly, the late postoperative stage is defined as the initial 6 weeks to 3 months; it refers to the time from hospital discharge to regaining preoperative health and well‐being 20 . It is well‐recognized that gender and age above 60 years are significantly associated with length of hospital stay 21 .…”
mentioning
confidence: 99%
“…19 Importantly, the late postoperative stage is defined as the initial 6 weeks to 3 months; it refers to the time from hospital discharge to regaining preoperative health and well-being. 20 It is well-recognized that gender and age above 60 years are significantly associated with length of hospital stay. 21 Therefore, omitting these patient details renders it challenging to fairly assess the quality of the study findings in the context of all cardiac patients undergoing surgery.…”
mentioning
confidence: 99%
“…Rahman et al found that patients with uncontrolled diabetes mellitus, hypertension, chronic obstructive pulmonary disease, and use of antidepressant drugs had worse recovery postsurgery. 14 …”
mentioning
confidence: 99%